2022
DOI: 10.3390/pr10050919
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Hyperglycemic Effect of Magnesium-Enhanced Alkaline-Reduced Water on High Glucose-Induced Oxidative Stress in Renal Tubular Epithelial Cells

Abstract: Diabetes is coupled with hyperglycemia, a state in which elevated glucose levels trigger oxidative stress (OS) in various body functions. One of the organs most afflicted by diabetes is the kidney. Despite this, specific treatments to mitigate the harmful effects of hyperglycemia-induced OS in the kidney have not been extensively explored. This study evaluates the anti-hyperglycemic efficacy of magnesium-enhanced alkaline-reduced water (MARW) in human kidney-2 (HK-2) cells. OS, mitogen-activated protein kinase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 57 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Similarly, XAV-939 has been shown to target the Wnt/B-catenin signaling pathway by inhibiting tankyrases 1 and 2. It has been demonstrated that targeting the Wnt/B-catenin signaling pathway is effective in many cancers that includes breast cancer, colorectal cancer and WTK1 human lymphoblastoid cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, XAV-939 has been shown to target the Wnt/B-catenin signaling pathway by inhibiting tankyrases 1 and 2. It has been demonstrated that targeting the Wnt/B-catenin signaling pathway is effective in many cancers that includes breast cancer, colorectal cancer and WTK1 human lymphoblastoid cells [ 42 ].…”
Section: Discussionmentioning
confidence: 99%